1976
DOI: 10.1111/j.1651-2227.1976.tb04943.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cornelia De Lange's Syndrome

Abstract: A prevalence investigation of Cornelia de Lange's syndrome in Denmark is presented. The patients were traced by screening all institutional mentally retarded patients, patients in schools and kindergartens for imbecile patients and finally by getting information on Cornelia de Lange patients known to pediatric departments. In this way 24 patients, 10 men and 14 women, were found. This amounts to a population prevalence of 0.5/100 000. Clinical data, histories of the patients and genealogical data are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 9 publications
1
37
0
1
Order By: Relevance
“…Our survey confirmed many of the findings previously documented in BDLS including absence of speech [Barr et al, 1971;Beck, 1976;Berg et al, 1970;Johnson et al, 19761, feeding [Barr et al, 1971;Beck, 1976;Begemen and Duggan, 19761 and behavioral p e r g et al, 1970;Johnson et al, 1976;Greenberg and Colesman, 19731 problems, and dental abnormalities [Barr et al, 1971, Begemen andDuggan, 1976;Berg et al, 19701. We also noted the presence of genital abnormalities in males and hearing loss.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our survey confirmed many of the findings previously documented in BDLS including absence of speech [Barr et al, 1971;Beck, 1976;Berg et al, 1970;Johnson et al, 19761, feeding [Barr et al, 1971;Beck, 1976;Begemen and Duggan, 19761 and behavioral p e r g et al, 1970;Johnson et al, 1976;Greenberg and Colesman, 19731 problems, and dental abnormalities [Barr et al, 1971, Begemen andDuggan, 1976;Berg et al, 19701. We also noted the presence of genital abnormalities in males and hearing loss.…”
Section: Discussionsupporting
confidence: 92%
“…Although one study [Motl and Opitz, 19711 has also reported a female preponderance for BDLS subjects, this has not been seen in other studies [Beck, , 1976;Halal and Preus, 19791. It is possible that heterogeneity of subjects, engendered by different diagnostic criteria in different surveys, could be responsible for the differences among surveys on this point.…”
Section: Discussionmentioning
confidence: 74%
“…Cornelia de Lange syndrome (CdLS) is a rare genetic syndrome with an estimated prevalence of 1:50,000 births (Beck, 1976;Beck & Fenger, 1985) and is caused by a deletions on chromosomes 5, 10 and X Krantz et al, 2004;Tonkin, Wang, Lisgo, Bamshad & Strachan, 2004;Musio et al, 2006;Deardorff et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…CdLS is a multiple congenital anomaly/mental retardation syndrome that was first described in 1933 by the Dutch pediatrician Cornelia de Lange, and is currently estimated to have a prevalence of 0.6-10 per 100,000 individuals [Silver, 1964;Beck, 1976;Filippi, 1989]. It is characterized by a widely varying phenotypic severity and its diagnosis is still typically clinical, although it has recently been reported that a significant proportion of CdLS patients carry a mutation in the NIPBL gene with a dominant pattern of inheritance Krantz et al, 2004].…”
Section: Introductionmentioning
confidence: 99%